INDEKS KEPUASAN MASYARAKAT PADA PELAYANAN PAJAK KENDARAAN BERMOTOR DI MAL PELAYANAN PUBLIK KOTA SURAKARTA TAHUN 2023 - Nur, Aji Muhammad; Suranto, Joko; Suhita, Damayanti (Solidaritas, 2024)
This research aims to describe the Community Satisfaction Index for motor vehicle tax services at the Surakarta City Public Service Mall. This research is quantitative research using descriptive research methods which are analyzed using the Community Satisfaction Index analysis technique. This research uses the Service Triangle theory proposed by Alberch and Zemke which is measured using 10 indicators divided into these three aspects. This research was conducted at the Surakarta City Public Service Mall in January 2024. The sampling technique used a non-probability sampling technique with simple random sampling. The data collection techniques used in this research are Questionnaires, Documentation and Literature Study. From the research results, it was found that the highest interval value or average value of the aspects depicted in the Service Triangle was 3.62 and the lowest interval value or average value was 3.51. These values ​​are found in the aspects: Service Strategy 3.56 is included in the "Very Good" performance category, Service System 3.51 is included in the "Good" performance category, Human Resources 3.62 is included in the "Very Good" performance category. Overall the Public Satisfaction Index for Motor Vehicle Tax Services at Public Service Malls reached 3.56 with a conversion value of 88.88 which is included in the "A" or "Very Good" category. Keywords : Public Service, Community Satisfaction Index.